Myocardial Uptake of Technetium-99m-Furifosmin (Q12) Versus Technetiiim-99m-Sestamibi (MIBI) - Bangard, M.; Bender, H.; Grünwald, F.; Hümmelgen, Melanie; Willkomm, Petra; Palmedo, H.; Lüderitz, B.; Biersack, H.-J. (Nuklearmedizin - NuclearMedicine, 1999)
Aim: This study was performed to compare the myocardial uptake of Tc-99m-furifosmin (Q12) versus Tc-99m-sestamibi (MIBI) in correlation to the whole-body uptake under resting conditions. Methods: 21 patients with coronary artery disease and no rest ischemia were examined. A whole-body scan was performed 60 min. p.i. under resting conditions. A quantification of the uptake (whole-body, heart and right lung) was done by ROI technique. Results: The heart-to-lung ratio of Q12 (1.56 ± 0.191) was significantly lower as compared to MIBI (1.94 ± 0.197; p <0.01). In contrast, the heart-to-whole-body ratios (Q12 versus MIBI: 0.027 ± 0.012 versus 0.026 ± 0.004; p <0.76) did not differ. The lung-to-whole-body ratio (Q12 versus MIBI: 0.018 ± 0.009 versus 0.013 ± 0.002; p <0.17) were different, but did not reach significance. Conclusion: These data show that under resting conditions the total myocardial uptake of Q12 does not differ significantly from that of MIBI. However, the pulmonary uptake of Q12 is slightly higher, resulting in a significant lower heart-to-lung ratio. These findings imply a lower image quality of Q12 compared to MIBI.
Keywords: Tc-99m-furifosmin: Q12; Tc-99m-sestamibi; MIBI-Myocardial Uptake